Determination of Standard Levels for Components of Health-Related Physical Fitness Using Computer Program - عطا الله, أحمد; دحون, العمري; طاهر, طاهر (International Journal of e-Healthcare Information Systems (IJe-HIS), 2015)
This study is aimed to design a computer program to assess the elements of health-related fitness for secondary students and determine their levels in the light of the proposed application software. To achieve this, the researchers adopted the descriptive style survey sample which was selected randomly from secondary students of some high schools of the state of Relizane who were numbered 2013 pupils. There has been using the battery tests which have included five tests, they are: body mass index, pacer test, push-up test, curl-up test and sit and reach test. The results have shown the effectiveness of the proposed software in the evaluation of the elements of health-related fitness at secondary school pupils to a large number of students in less time and effort and more accurate.
Keywords: Determination of Standard Levels for Components of Health -Related Physical Fitness Using Computer Program